1966
DOI: 10.1002/1097-0142(196606)19:6<781::aid-cncr2820190607>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications of acute leukemia

Abstract: The lungs of 50 consecutive autopsied cases of acute leukemia were studied and cultures were obtained from 36. Thirty-one patients had major pulmonary lesions. Most of these were not recognizcd antemortem. Infection was the most common pulmonary complication. Pulmonary disease was present in 95% of those cases with abnormal chest x-rays but 59% of the patients with normal chest x-rays also had pulmonary pathology. Leukemic involvement was identified microscopically in 64% of the lungs. Peribronchial infiltrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
6

Year Published

1968
1968
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(46 citation statements)
references
References 23 publications
2
38
0
6
Order By: Relevance
“…In our experience, in agreement with other experiences [2,3,17] MDP was observed in 25/80 (31.2%) cases of patients with leukemia in induction therapy. Although fungal pneumonias are common in advanced phases of leukemias, they can be present in patients at disease onset; in our study, in 3 cases (12%) the BAL was positive for Aspergillus (2 A. fumigatus and 1 A. niger ), the CT was highly suggestive of disease caused by filamentous fungi and fungal pneumonia was considered probable.…”
Section: Discussionsupporting
confidence: 93%
“…In our experience, in agreement with other experiences [2,3,17] MDP was observed in 25/80 (31.2%) cases of patients with leukemia in induction therapy. Although fungal pneumonias are common in advanced phases of leukemias, they can be present in patients at disease onset; in our study, in 3 cases (12%) the BAL was positive for Aspergillus (2 A. fumigatus and 1 A. niger ), the CT was highly suggestive of disease caused by filamentous fungi and fungal pneumonia was considered probable.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with acute leukaemia the diagnosis is more difficult. Various infections may present with the clinical picture of pulmonary oedema (Bodey, Powell, Hersh, Yeterian, and Freireich, 1966). In any suspected case of Pneumocystis carinii pneumonia chest radiographs may be helpfui, as illustrated by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most important factor in predicting the risk of infection is the duration of neutropenia: it was reported that there was a 60% risk of developing infection if neutropenia persisted for 3 weeks, with a further rise to 100% when the neutrophil count was below 0.10 Â 10 9 /l. Not only is the incidence of infections related to neutrophil count, but also the outcome: the highest percentage of death occurs among patients with persistent severe neutropenia [27].…”
Section: Neutropeniamentioning
confidence: 99%